Preparação e Caracterização de Compostos Fe-Al-O pelo processo Sol- Gel - Bini, Marcia Ferreira (2009)
In this work the central proposition is the synthesis and the characterization of polycrystalline mixed oxides materials (Fe-Al-O system), in the nanometric scale (nanometric powders). Among the possibilities of this system, the hematite ( -Fe2O3), that is isomorph to the alumina ( -Al2O3) presents interesting magnetic properties. Besides that, the FeAlO3 phase presents a multiferroic magnetoelectric behavior. The studies were conducted with the plan of understand and explore the modifications and the structural evolution of the iron doped Alumina. This way, in this work it was studied the preparation and characterization (thermal, structural, microstructural and spectroscopic) of the Fe-Al-O family compounds obtained by sol-gel chemistry. The characterizations were obtained through X-ray diffraction, Fourier transform infrared spectroscopy, thermogravimetric analysis, differential thermal analysis, scanning electron microscopy and energy dispersive X-ray spectroscopy measurements. The thermogravimetric and differential thermal analyses showed that the formation of the interest oxides systems happens above 600 oC. This way, we achieved heat treatments in the samples in temperatures between 700 and 1300°C. The obtained samples after the heat treatments were analyzed through X-ray diffraction, with subsequent structural refinement using the LeBail method, scanning electron microscopy and energy dispersive X-ray spectroscopy measurements. The energy dispersive X-ray spectroscopy measurements showed that the measured stoichiometries are a little moved of the proposed nominal stoichiometries, except for the 50% Fe - 50% Al sample, which possesses a very close stoichiometry related to the nominal value. Thus, we concluded that the mixed oxides materials production technique, using NH4OH as complexing agent, it is very efficient, so much in the production of the solid solutions as in the production of FeAlO3 compound.